Pengaruh Sosial Ekonomi Terhadap Kepemilikan Jaminan Kesehatan Tenaga Kerja Informal di Sumatera Utara - Ahmad Fauzi Haqiqi Rangkuti, Ahmad Fauzi Haqiqi Rangkuti; Urmatul Uska Akbar (Media Riset Ekonomi Pembangunan (MedREP), 2024)
This research aims to determine the factors that influence the ownership of health insurance for informal workers in North Sumatra. This research is a quantitative research using secondary data from the 2023 National Socio-Economic Survey. The sample used was heads of households working in the informal sector aged 15-64 years in North Sumatra Province in 2023, namely 10,172 heads of households. The health insurance used in this research is BPJS (Social Security Administering Agency) non-PBI Health (Contribution Assistance Recipients), Private Insurance and Office or Company Health Insurance, and excludes BPJS (Social Security Administering Agency) PBI (Contribution Assistance Recipients) health insurance.) and JAMKESDA (Regional Health Insurance). The analysis used is descriptive analysis and inductive analysis. In inductive analysis, this research uses the logistic regression method. Logistic Regression Analysis is used to see the effect of the dependent variable on the independent variable where the dependent variable is binary, namely zero and one. The results of this study show that the variables per capita expenditure, education, age, number of family members, and area of ​​residence have a positive and significant effect on the ownership of health insurance for informal workers in North Sumatra. Heads of households with higher expenditure, high school education or above, unmarried, and residing in urban areas have greater opportunities to have health insurance than others.